2011
DOI: 10.1002/hep.24471
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of SIRT1 in livers of old mice leads to impaired body homeostasis and to inhibition of liver proliferation

Abstract: Age declines liver functions, leading to the development of age-associated diseases. A member of the sirtuins family, SIRT1, is involved in the control of glucose homeostasis and fat metabolism. Because aging livers have alterations in glucose and fat metabolism, we examined a possible role of SIRT1 in these alterations. We found that aged livers have a reduced expression of SIRT1 and have lost proper control of the regulation of SIRT1 after partial hepatectomy (PH). Down-regulation of SIRT1 in the liver of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 22 publications
3
86
1
Order By: Relevance
“…In addition, we observed an increase in hepatic oxidative stress, with multiple harmful consequences, that may derive from an imbalance between pro‐ and anti‐oxidants, together with increased hepatic lipid content, a well‐known source of cellular oxidative stress. In an important way, oxidative stress could also contribute to potentiate the senescence pathways, and vice versa, thus creating a deleterious vicious cycle in the aged liver (Jin, Iakova, Jiang, Medrano, & Timchenko, 2011; Sharpless & De Pinho, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed an increase in hepatic oxidative stress, with multiple harmful consequences, that may derive from an imbalance between pro‐ and anti‐oxidants, together with increased hepatic lipid content, a well‐known source of cellular oxidative stress. In an important way, oxidative stress could also contribute to potentiate the senescence pathways, and vice versa, thus creating a deleterious vicious cycle in the aged liver (Jin, Iakova, Jiang, Medrano, & Timchenko, 2011; Sharpless & De Pinho, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…One of the critical and early steps of the cascade of alterations in young S193D and old WT mice is the elevation of a dominant negative isoform of C/EBP␤, C/EBP␤-LIP. In addition to elevation of C/EBP␤-LIP, livers of S193D mice contain high levels of C/EBP␣-HDAC1 complexes that also repress C/EBP-dependent promoters (6,18). As the result, livers of old WT and young S193D mice contain high levels of two repressors of the gene expression, C/EBP␣-HDAC1 complexes and C/EBP␤-LIP.…”
Section: Discussionmentioning
confidence: 99%
“…We found that C/EBP␣ and C/EBP␤ also interact with these sites in liver nuclear extracts (data not shown). Our previous reports and studies of C/EBP␣ and FXR promoters in this work showed that, in S193D mice, C/EBP␣ forms complexes with histone deacetylase 1 (HDAC1) and these complexes repress target promoters (17,18). Given high affinity sites for C/EBP␣ and C/EBP␤-LIP within the TERT promoter, we examined the hypothesis that C/EBP␣-HDAC1 complexes and C/EBP␤-LIP repress the TERT promoter in livers of S193D mice.…”
Section: C/ebp␣-hdac1 Complexes and C/ebp␤-lip Inhibitmentioning
confidence: 94%
See 2 more Smart Citations